Root caries experience among Australian adults. (10th May 2017) - Hariyani, Ninuk; Spencer, A. John; Luzzi, Liana; Do, Loc Giang
Abstract : Background: Increase in life expectancy and tooth retention in contemporary Australian adults may increase population‐level burden of having root caries. This study aimed to describe patterns and evaluate associations of root caries with socio‐demographic, socio‐economic, clinical and behavioural factors. Methods: A secondary analysis was undertaken using data from the National Survey of Adult Oral Health 2004‐2006, which included 5505 randomly general adults 15+ years old. Participants underwent an oral examination and completed an interview and a questionnaire. Prevalence and mean number of decayed/filled root (root DFS), untreated root (root DS), filled root (root FS), gingival recession, oral hygiene and gingival status were derived from examinations. Socio‐demographic, socio‐economic and behavioural factors were self‐reported. Multivariable models were generated to estimate prevalence ratios (PR), mean ratios (MR) and confidence intervals (95% CI), adjusting for number of surfaces with gingival recession. Additional analysis for older adults 60+ years old was presented. Results: The prevalence of root caries was 25.3% (CI=23.6‐27.1) and 62.0% [CI=58.7‐65.1] among general and older adults, respectively. Risk factors found were similar in both populations. Smokers had higher prevalence and mean number of root DFS, DS and FS than never‐smokers. In contrast with poor oral hygiene, high income and frequent brushing were significantly associated with lower mean root DS. Frequent dental visiting was associated with higher root FS and DFS. Conclusions: Root caries affected about a quarter of Australian general adults and more than a half of older adults. People who were smokers presented a significantly higher prevalence and severity of root caries.